2019
DOI: 10.1017/s0021859619000236
|View full text |Cite
|
Sign up to set email alerts
|

Plant and animal responses of elephant grass pasture-based systems mixed with pinto peanut

Abstract: The effects of growing pinto peanut mixed with elephant grass-based pastures are still little known. The aim of the current research was to evaluate the performance of herbage yield, nutritive value of forage and animal responses to levels of pinto peanut forage mass mixed with elephant grass in low-input systems. Three grazing systems were evaluated: (i) elephant grass-based (control); (ii) pinto peanut, low-density forage yield (63 g/kg of dry matter – DM) + elephant grass; and (iii) pinto peanut, high-densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Regarding herbage accumulation, the values confirm thebeneficial effect of the presence of the pinto peanut, with a 27.5% increase in the pasture biomass. In a similar experiment, with 20% of the pinto peanut in the pasture composition, a previous study found an increase in forage production of 21% compared to pure grass pasture (Vieira et al 2019). A similar response was also obtained in a mixed pasture with elephantgrass and red clover (Diehl et al 2014).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Regarding herbage accumulation, the values confirm thebeneficial effect of the presence of the pinto peanut, with a 27.5% increase in the pasture biomass. In a similar experiment, with 20% of the pinto peanut in the pasture composition, a previous study found an increase in forage production of 21% compared to pure grass pasture (Vieira et al 2019). A similar response was also obtained in a mixed pasture with elephantgrass and red clover (Diehl et al 2014).…”
Section: Discussionmentioning
confidence: 57%
“…When well-managed under rotational stocking, elephantgrass can persist for decades (Olivo et al 2017). It is usually planted in monoculture with relatively high amounts of nitrogen fertilizer, making production more expensive and less sustainable (Vieira et al 2019). One of the ways to reduce these impacts is intercropping with forage legumes.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the post-grazing composition of pastures, less participation of ryegrass is evident due to the cows’ greater preference for winter species than for summer species (Vieira et al ., 2019). For the dead material fraction, an increase occurred due to the effect of trampling and self-shading (Alderman et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…than in the grass monocrop (46 vs 26 kg N/ha). Vieira et al (2019) reported an increase of 81% in dwarf elephant grass HA when forage peanut (Arachis pintoi Krap. & Greg.)…”
Section: Introductionmentioning
confidence: 99%